Reversing Titanium Oligomer Formation towards High‐Efficiency and Green Synthesis of Titanium‐Containing Molecular Sieves. Issue 7 (21st December 2020) - Lin, Dong; Zhang, Quande; Qin, Zhengxing; Li, Qing; Feng, Xiang; Song, Zhaoning; Cai, Zhenping; Liu, Yibin; Chen, Xiaobo; Chen, De; Mintova, Svetlana; Yang, Chaohe
Abstract: Green and efficient synthesis of titanium‐containing molecular sieves is limited by the quantity of environmentally unfriendly additives and complicated synthesis procedures required. Oligomerization of Ti monomers into anatase TiO2 is the typical outcome of such procedures because of a mismatch between hydrolysis rates of Si and Ti precursors. We report a simple and generic additive‐free route for the synthesis of Ti‐containing molecular sieves (MFI, MEL, and BEA). This approach successfully reverses the formation of Ti oligomers to match hydrolysis rates of Ti and Si species with the assistance of hydroxyl free radicals generated in situ from ultraviolet irradiation. Moreover, fantastic catalytic performance for propene epoxidation with H2 and O2 was observed. Compared with the conventional hydrothermal method, this approach opens up new opportunities for high‐efficiency, environmentally benign, and facile production of pure titanium‐containing molecular sieves. Abstract : A reversed‐oligomerization approach was developed for preparation of titanium‐containing molecular sieves. The highly efficient and simple approach eliminates additives and it produces molecular sieves in high yield with improved titanium distribution, smaller particle sizes, and a higher surface area compared to previously reported methods. The approach is generic and can be applied in the synthesis of different molecular sieves (for example, MFI, MEL, BEA).